Capitals of the Spanish province and commemorative spaces during the Franco era - Díaz del Campo, Ramón Vicente (2023)
This article reflects on the creation of monumental sculpture in Spanish provincial capitalsduring the 1950s and 1960s and the role they play on the dimensions of the collective memoryof those cities.In the first part of this article studies the relationship between art, historical memory andnational identity, with special interest regarding the Spanish context. This space endowedwith political symbolisms of great significance to Franco’s dictatorship, although the monumental sculptures experienced many upheavals and singular cases. Historical identities usedto be understood as a permanent background, where it is always possible to find prominentfigures in order to give form to the different narratives.